Using Multiple Exemplar Training to Teach Basic Theory-of-Mind Skills to Adolescents With Autism Spectrum Disorder Authors Fuxin LianORCID IDGabrielle T. LeeORCID IDYan LongWeina MaMian Wang - Fuxin Lian; Gabrielle T. Lee
Adolescents with autism spectrum disorder (ASD) seem to have difficulty dealing with complex social situations, which is likely related to their challenges in understanding others$1 (Bperspectives, according to the Theory of Mind (ToM). The purpose of this preliminary study was to examine the effect of multiple exemplar training (MET) on the acquisition, maintenance, and generalization of basic theory-of-mind skills in three Chinese adolescents with ASD by employing a single-case, multiple-probe design. Results suggest that MET was effective in the acquisition and maintenance phases of training for improving all three participants$1 (Btarget ToM skills and their ToM assessment scores. The participants also demonstrated increased appropriate social interactions and decreased inappropriate social interactions with peers during indoor recess, indicating that MET is effective in helping adolescents with ASD generalize ToM skills to natural settings.s